2006
DOI: 10.7771/1541-5015.1006
|View full text |Cite
|
Sign up to set email alerts
|

The 3C3R Model: A Conceptual Framework for Designing Problems in PBL

Abstract: Well-designed problems are crucial for the success of problem-based learning (PBL). Previous discussions about designing problems for PBL have been rather general and inadequate in guiding educators and practitioners to design effective PBL problems. This paper introduces the 3C3R PBL problem design model as a conceptual framework for systematically designing optimal PBL problems. The 3C3R model comprises two classes of components: core components and processing components. Core components-including content, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
179
0
40

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 175 publications
(220 citation statements)
references
References 45 publications
1
179
0
40
Order By: Relevance
“…However, our students maintained that although this is well received there is a danger, as warned by Hung, for students to compartmentalize knowledge and lose sight of the overview (Hung 2006). The critics of our application of PBL to one module only would argue that the connection of concepts emerges slowly over time in a full PBL curriculum (Conway and Little 2000).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, our students maintained that although this is well received there is a danger, as warned by Hung, for students to compartmentalize knowledge and lose sight of the overview (Hung 2006). The critics of our application of PBL to one module only would argue that the connection of concepts emerges slowly over time in a full PBL curriculum (Conway and Little 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been observed that students have a tendency not to be intrinsically apt to integrate what they have learned (Dolmans et al 1993;Drummond-Young and Mohide 2001;Lieux 2001). If the PBL curriculum provides no means for facilitating students to engage in a knowledge integration process and see the interconnections among the constituents (concepts, principles, procedures, and factual information) within a subject domain, students' "problem-packaged" knowledge could become "compartmental" knowledge (Hung 2006). Thus, students may be able to see the forest floor but not the landscape.…”
Section: Literature Review: the Concept Of Connection In Pbl Curriculamentioning
confidence: 99%
See 3 more Smart Citations